Positive Affect and Cognitive Functioning in Older African American Adults. (20th December 2022) - Halter, Colt M; Moll, Allison C.; Kero, Katherine; Hanna, Sophie; DiCerbo, Loraine M.; Woodard, John L.; Giordani, Bruno; Daugherty, Ana M.; Kavcic, Voyko
Abstract: Background: Previous research has demonstrated a link between affect and cognitive functioning, particularly showing that negative affect is related to lower cognitive performance across several cognitive domains. However, the relationship between positive affect (PA) and cognitive functioning is not as thoroughly characterized, though some previous work suggests that PA may be related to improved memory consolidation and greater cognitive flexibility. There is little research, if any, on the relation between PA and cognition in older adults from diverse racial backgrounds, who are also at greater risk for Alzheimer's disease. PA may be a modifiable factor and target for intervention to deter cognitive decline. Therefore, we investigated whether PA was related to cognitive functioning in a sample of community‐dwelling, older African American adults. We predicted that greater PA would be associated with greater global cognitive functioning, immediate memory recall, and delayed memory recall while controlling for age. Method: Telephone screenings were administered to 194 older African Americans (aged 64‐94 years). Global cognitive functioning, immediate recall, and delayed recall were measured via the Telephone Interview for Cognitive Status‐Modified (TICSm). Immediate and delayed recall scores were excluded from global cognitive functioning scores to reduce conceptual overlap. PA was measured with a questionnaire of emotional functioning. We used hierarchical linear regression to determine whether PA was positively associated with cognitive functioning while controlling for age. Result: Higher PA was predictive of greater global cognitive functioning, after accounting for the effect of age ( F (2, 191) = 15.70, p <.001; ΔR 2 = .05, b = 0.68, SE = 0.21, p = .002). Similarly, higher PA was predictive of greater immediate recall ( F (2, 191) = 14.10, p <.001; ΔR 2 = .03, b = 0.45, SE = 0.19, p = .019) and delayed recall ( F (2, 191) = 7.44, p <.001; ΔR 2 = .02, b = 0.48, SE = 0.23, p = .035). Conclusion: In support of our hypothesis, we have demonstrated that greater PA is associated with greater global cognitive functioning, immediate memory recall, and delayed memory recall among older African American adults. Past studies report some relationships between PA and cognition, though little, if any, work has been done with aging adults from diverse racial backgrounds. Understanding how PA relates to cognition in late life is crucial because it may be a modifiable protective factor and a target for intervention.